Day of the Dead in the USA : the migration and transformation of a cultural phenomenon - Marchi, Regina M., 1965- (New Brunswick, New Jersey : Rutgers University Press, 2009)
Honoring relatives by tending graves, building altars, and cooking festive meals has been an honored tradition among Latin Americans for centuries. The tribute, "el Dia de los Muertos," has enjoyed renewed popularity since the 1970s when Latino activists and artists in the United States began expanding "Day of the Dead" north of the border with celebrations of performance art, Aztec danza, art exhibits, and other public expressions. Focusing on the power of ritual to serve as a communication medium, Regina M. Marchi combines a mix of ethnography, historical research.
An ancient and modern festival -- Mexico's special relationship with Day of the Dead -- Day of the Dead in the United States -- Ritual communication and community building -- U.S. Day of the Dead as political communication : a moral economy -- Day of the Dead in the U.S. media : the celebration goes mainstream -- The expanding hybridity of an already hybrid tradition -- The commoditization of a death ritual.
Includes bibliographical references (pages 171-184) and index.
Description based on online resource; title from digital title page (viewed on December 19, 2022).
English.
JSTOR
Keywords: All Souls' Day -- United States; United States -- Social life and customs; United States -- Religious life and customs; Jour des morts -- États-Unis.; États-Unis -- Mœurs et coutumes; SOCIAL SCIENCE -- Holidays (non-religious); SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies; All Souls' Day; Manners and customs; United States